2019
DOI: 10.1093/pcp/pcz052
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Suppresses Brassica napus Seed Oil Accumulation by Inhibition of Photosynthesis and BnWRI1 Pathway

Abstract: Heat stress during Brassica napus seed filling severely impairs yield and oil content. However, the mechanisms underlying heat-stress effects on B. napus seed photosynthesis and oil accumulation remain elusive. In this study, we showed that heat stress resulted in reduction of seed oil accumulation, whereas the seed sugar content was enhanced, which indicated that incorporation of carbohydrates into triacylglycerols was impaired. Photosynthesis and respiration rates, and the maximum quantum yield of photosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
2
44
1
Order By: Relevance
“…These results correlate with earlier studies (Aksouhet al 2001;Aksouh-Harradj et al 2006) of intense temperature exposure during seed maturation but contrast with others that highlighted increased total FA contents under a long mild stressing event (Brunel-Muguet et al 2015). Disruption of FA accumulation in OSR has been shown under intense heat stress across a range of temperatures similar to those imposed under our heat-peak conditions, and this was a consequence of photosynthesis inhibition and downregulation of BnWRI1 gene expression, which is a key regulator of FA biosynthesis (Ruuska, Girke, Benning & Ohlrogge 2002;Huang et al 2019). Our results also revealed higher total FA, SFA, and UFA concentrations under LS, but only in specific high-temperature sequences (Figure 2), which contrasted with prior results (Brunel-Muguet et al 2015).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…These results correlate with earlier studies (Aksouhet al 2001;Aksouh-Harradj et al 2006) of intense temperature exposure during seed maturation but contrast with others that highlighted increased total FA contents under a long mild stressing event (Brunel-Muguet et al 2015). Disruption of FA accumulation in OSR has been shown under intense heat stress across a range of temperatures similar to those imposed under our heat-peak conditions, and this was a consequence of photosynthesis inhibition and downregulation of BnWRI1 gene expression, which is a key regulator of FA biosynthesis (Ruuska, Girke, Benning & Ohlrogge 2002;Huang et al 2019). Our results also revealed higher total FA, SFA, and UFA concentrations under LS, but only in specific high-temperature sequences (Figure 2), which contrasted with prior results (Brunel-Muguet et al 2015).…”
Section: Discussionmentioning
confidence: 53%
“…Other phytohormones were shown to be involved in the control of secondary dormancy, defined as failure in the germination process of mature and non-dormant seeds under adverse conditions (Pekrun, Lutman & Baeumer 1997). Recent studies have highlighted the role of indole-3-acetic acid (IAA), whose concentrations increase in dormancy-induced seeds (Shu, Liu, Xie & He 2016;Liu et al 2019;Tuan, Yamasaki, Kanno, Seo & Ayele 2019). Its high levels have also been correlated with high jasmonic acid (JA) in seeds as a consequence of both phytohormones interacting during the expression of indole glucosinolate biosynthesis genes (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-temperature treatments induce changes in seed oil content and photosynthesis activity. It suggested that the damage to PSII and inhibition of a fatty acid biosynthesis pathway controlled by the transcription factor BnWRI1 might be the major causes of the decreased oil content of B. napus seeds that develop under HS (Huang et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of gene expression is a popular approach to study various biological phenomena [1][2][3][4][5][6][7][8] . Recently, large-scale transcriptome analysis by RNA-Seq of hundreds of samples has been emerged in plant biology [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%